(untitled) (diségno, 2023)
On December 2nd and 3rd, 2022, in conjunction with the International Day of Persons with Disabilities (celebrated on December 3 each year since 1981), the first edition of the international conference DAI. Il Disegno per l’Accessibilità e l’Inclusione (DAI. Drawing for Accessibility and Inclusion) was held in Genoa. This is an interdisciplinary discussion space created for the presentation and sharing of application experiences and research activities focused on the issues of accessibility and inclusion, and linked by the use of knowledge, methods and tools peculiar to the discipline of Drawing. [read more]